The impact of different history curricula on Somali students’ patriotism - Muse, Mohamamud Yousuf; Shuriye, Abdi Omar (Australian Journal of Islamic Studies, 2018)
This study explores the perception of secondary history curricula among Somali students in Malaysian institutions of higher education. To the researcher’s knowledge, no study has examined the impact of different history curricula on Somali students’ patriotism. This study developed a questionnaire survey based on two research questions. The research participants were undergraduates selected from different Malaysian institutions of higher education: International Islamic Universiti Malaysia (IIUM), Utara Universiti Malaysia (UUM), Universiti Technology Malaysia (UTM), Universiti Tun Hussein Onn Malaysia (UTHM) and others. This study explored three latent constructs of secondary history curricula underpinning the integration among students: (i) knowledge, (ii) loyalty and (iii) behavior. The covariance correlations were statistically significant among the three factors for secondary history curricula. This study employed exploratory factor analysis (EFA) to examine latent constructs underlying the dimensions of secondary history validity. It also found that the three constructs have a direct influence on Somali students’ patriotism. For the study, 450 survey questionnaires were disseminated, of which 350 were returned. With regard to theoretical contributions, the research contributes by promoting a number of new, consistent and suitable construct estimations within an academic application. This research has showed that the underlying dimensions explored influence students’ perceptions towards loyalty to their country. Teaching common or standardized History syllabuses which carry similar knowledge, loyalty and behavior can enhance the sense of nationalism among students and foster integration and peace among them. The assessment structure of underlying dimensions was comparatively invariant across the three different groups. The finding of this research also contribute to the body of knowledge by exploring the factors in history curricula that influence patriotism among students in Malaysian institutions of higher education.